Spin-on carbon hard mask composition with low evaporation loss and patterning method using same

JP7652937B2Active Publication Date: 2025-03-27YOUNG CHANG CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023569809
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-17
Filing Date
2022-05-03
Publication Date
2025-03-27
Estimated Expiration
2042-05-03

AI Technical Summary

Benefits of technology

【0012】 本発明による蒸発減量(evaporation loss)を最小限に抑えることができるハードマスク組成物は、優れた耐熱性特性を有することにより、蒸発減量を最小限に抑えてディフェクト(defect)を減らすことができ、エッチ(etch)選択性が高く、多重エッチに対する耐性が十分であるため、半導体微細パターンの形成時に優れた性能を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652937000041
    Figure 0007652937000041
  • Figure 0007652937000001
    Figure 0007652937000001
  • Figure 0007652937000002
    Figure 0007652937000002
Patent Text Reader

Abstract

The present invention has an object to provide a hard mask composition having low evaporation loss, which is useful for semiconductor lithography processes, and comprises a spin-on hard mask composition comprising a polymer represented by Chemical Formula 1, a surfactant and an organic solvent, and a patterning method using the composition. The hard mask according to the present invention has excellent heat resistance properties, and therefore has the effect of improving yield by minimizing evaporation loss that may act as defects during processing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard mask composition having low evaporation loss, which is useful in semiconductor lithography processes. More specifically, the present invention relates to a hard mask composition having excellent heat resistance properties, which can minimize evaporation loss that may act as a defect during processing, and a patterning method using the composition. [Background technology]

[0002] In recent years, with the miniaturization and integration of semiconductor devices, there is a demand for finer patterns. As a method for forming such fine patterns, it is efficient to develop exposure equipment or introduce additional processes to finer photoresist patterns. Higher resolution photoresists and photolithography processing tools are being developed as a way to increase the integration density of semiconductor devices and enable the creation of finer structures having dimensions in the nanometer range. In the past, semiconductor manufacturing processes used i-line light sources with a wavelength of 365 nm to form patterns on semiconductor substrates, but light sources with smaller wavelength bands are now required to form finer patterns. In fact, lithography technology using light sources such as KrF (248 nm), ArF (193 nm), and EUV (Extreme Ultra Violet, 13.5 nm) has been developed and is currently either commercialized or in the process of being commercialized, making it possible to realize finer wavelengths.

[0003] As the size of the pattern becomes smaller, the thickness of the photoresist becomes thinner to prevent the photoresist pattern from collapsing. Since it is no longer possible to etch the layer to be etched using the thinner photoresist pattern, a film with excellent etching resistance is introduced between the photoresist layer and the layer to be etched. This film is called a hard mask. The hard mask process refers to a process in which a hard mask is etched and patterned using a photoresist pattern, and then the layer to be etched is etched using the hard mask pattern. The hard mask film is manufactured by a CVD (Chemical Vapor Deposition) method or a spin on coating method. Hard mask films manufactured by the CVD method have drawbacks such as increased initial costs and process time due to the use of deposition machines, as well as particle issues. Therefore, efforts have been made to reduce costs and process time by using materials that can be spin-coated rather than deposition for the hard mask process. The spin-on coating method for hard mask processing has the advantages of lower initial investment costs compared to the CVD method, uniform coating properties, easy control of coating thickness, and reduced processing time. Meanwhile, as semiconductor processes have become more miniaturized recently, line widths have become narrower while heights have remained the same or become relatively higher, resulting in higher aspect ratios of patterns. As the height of the hard mask layer increases, there has been a problem in that defects occur due to increased evaporation loss during a baking process, resulting in reduced yields. Therefore, there is a need to develop new hard mask film materials that can improve yields by minimizing the evaporation loss that acts as a defect. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Korean Patent Publication No. 10-1777687 (September 12, 2017) [Patent Document 2] Korean Patent Publication No. 10-2240213 (April 14, 2021) Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention relates to a patterning method and composition using a spin-on carbon hard mask during a semiconductor manufacturing process, and aims to provide a spin-on carbon hard mask composition that can minimize evaporation loss that acts as a defect, and a patterning method using the same. [Means for solving the problem]

[0006] According to one aspect of the present invention, there is provided a spin-on carbon hard mask composition having a structure represented by the following chemical formula 1, a weight average molecular weight of 1,500 to 20,000, and capable of minimizing evaporation loss.

[0007] [ka]

[0008] In the formula, m and n are in the ranges of 1≦m≦50 and 1≦n≦50, respectively; R1 is, TIFF0007652937000002.tif7573, TIFF0007652937000003.tif5447, TIFF0007652937000004.tif5475, TIFF0007652937000005.tif5460, TIFF0007652937000006.tif6164, TIFF0007652937000007.tif4268, TIFF0007652937000008.tif4261, R2 is TIFF0007652937000009.tif2957, TIFF0007652937000010.tif2969, TIFF0007652937000011.tif3277, TIFF0007652937000012.tif3377, It contains one of the following files: TIFF0007652937000013.tif2461.

[0009] According to one embodiment of the present invention, the composition can contain, relative to the total weight of the composition, 1 to 50% by weight of the polymer represented by Chemical Formula 1, 50 to 98.99% by weight of an organic solvent, and 0.01 to 0.1% by weight of a surfactant. According to one embodiment of the present invention, the organic solvent may be one selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone, cyclopentanone, γ-butyrolactone, ethyl lactate (EL), methyl ethyl ketone, n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more thereof.

[0010] According to one embodiment of the present invention, the surfactant may be one selected from the group consisting of nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitan, or a mixture of two or more thereof.

[0011] According to another aspect of the present invention, there is provided a patterning method, comprising: applying the composition on a layer to be etched by spin coating; and then performing a baking process to form a hard mask film layer. According to another aspect of the present invention, the baking step can be carried out at a temperature of 150° C. to 400° C. for 1 minute to 5 minutes to form a pattern. Effect of the Invention

[0012] The hard mask composition according to the present invention, which can minimize evaporation loss, has excellent heat resistance properties, thereby minimizing evaporation loss and reducing defects, and has high etch selectivity and sufficient resistance to multiple etch processes, thereby providing excellent performance when forming semiconductor fine patterns. [Brief description of the drawings]

[0013] [Figure 1] 1 is a TGA spectrum of the polymer produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in more detail. The present invention relates to a spin-on carbon hard mask composition comprising a polymer having a structure represented by the following chemical formula 1 and having a weight average molecular weight of 1,500 to 20,000, preferably 1,500 to 15,000, and more preferably 1,500 to 10,000.

[0015] [ka]

[0016] In the formula, m and n are in the ranges of 1≦m≦50 and 1≦n≦50, respectively; R1 is, TIFF0007652937000015.tif7573, TIFF0007652937000016.tif5447, TIFF0007652937000017.tif5475, TIFF0007652937000018.tif5460, TIFF0007652937000019.tif6164, TIFF0007652937000020.tif4268, TIFF0007652937000021.tif4261, R2 is TIFF0007652937000022.tif2957, TIFF0007652937000023.tif2969, TIFF0007652937000024.tif3277, TIFF0007652937000025.tif3377, It contains one of the following: TIFF0007652937000026.tif2461.

[0017] In the above formula, R1 mainly serves to improve the thermal curing reactivity and etch selectivity of the whole polymer structure. In the formula, R2 plays a role in increasing the flowability and coatability of the polymer material formed mainly under acid catalyzed conditions. The polymer represented by the above chemical formula 1 is characterized in that it has a weight average molecular weight of 1,500 to 0,000, preferably 1,500 to 15,000, and more preferably 1,500 to 10,000.

[0018] When the weight average molecular weight of the polymer represented by Formula 1 is less than 1,500, a sufficient amount of polymer structure is not generated, resulting in reduced etch resistance, and when the weight average molecular weight is more than 20,000, the physical properties of the coated surface may be non-uniform. The hard mask composition may contain, relative to the total weight of the composition, 1 to 50% by weight of the polymer represented by Chemical Formula 1, 50 to 98.99% by weight of an organic solvent, and 0.01 to 0.1% by weight of a surfactant.

[0019] Here, if the polymer component is less than 1 wt % or more than 50 wt %, the coating thickness will be less than or more than the desired thickness, making it difficult to accurately adjust the coating thickness, and if the coating thickness exceeds the desired thickness, the coating properties may be poor. The organic solvent may be one selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone, cyclopentanone, γ-butyrolactone, ethyl lactate (EL), methyl ethyl ketone, n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more thereof.

[0020] The surfactant can be one selected from the group consisting of nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitans, or a mixture of two or more of these surfactants. The surfactant can be useful for coating properties and gapfill performance by lowering surface tension and increasing spreading and permeability. According to another embodiment of the present invention, there is provided a patterning method, comprising applying the composition on a layer to be etched by spin coating, and then performing a baking process to form a hard mask layer.

[0021] The composition can be spin-coated to a thickness of 135 to 2,200 nm. If the thickness is less than 135 nm, the composition is not sufficiently coated, resulting in a decrease in etch resistance, and if the thickness is more than 2,200 nm, the physical properties of the coating surface become non-uniform, resulting in poor coating properties, and therefore this cannot be adopted. The baking process can be performed for 1 to 5 minutes at a temperature of 150° C. to 400° C. During the baking process, the composition can undergo a self-crosslinking reaction.

[0022] Hereinafter, preferred examples and comparative examples of the present invention will be described. However, the following examples are merely preferred examples of the present invention, and the present invention is not limited to the following examples. EXAMPLES

[0023] [ka]

[0024] 40g of 9,9-bis(6-hydroxy-2-naphthyl)fluorene, 16g of 4,4-bismethoxymethylbiphenyl, and 150g of propylene glycol monomethyl ether acetate (PGMEA) were added to the flask and a nitrogen atmosphere was created. 0.20g of diethyl sulfate was added thereto, and the solution was heated to 140°C and refluxed for 10 hours. After the reaction was completed, the solution was purified with a hexane / ethanol / water (1:1:1) solution, recrystallized with an ethanol / water (10:1) solution, and then vacuum dried. As a result of GPC measurement, a polymer compound having a weight average molecular weight (Mw) of 5,000 based on standard polystyrene was obtained. EXAMPLES

[0025] [ka]

[0026] Except for heating the solution at 140° C. and refluxing it for 5 hours, the synthesis was carried out in the same manner as in Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 1,500. EXAMPLES

[0027] [ka]

[0028] The synthesis was carried out in the same manner as in Example 1, except that 0.40 g of diethyl sulfate was added, the solution was heated at 140° C., and then refluxed for 20 hours. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 10,000. EXAMPLES

[0029] [ka]

[0030] Except for adding 11 g of 1,3-bismethoxymethylbenzene instead of 4,4-bismethoxymethylbiphenyl, the synthesis was carried out in the same manner as in Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated in terms of standard polystyrene was 4,500. EXAMPLES

[0031] [ka]

[0032] Except for adding 13 g of 4,4-bismethoxymethylbiphenyl ether instead of 4,4-bismethoxymethylbiphenyl, the synthesis was carried out in the same manner as in Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated in terms of standard polystyrene was 5,200.

[0033] Comparative Example 1

[0034] [ka]

[0035] 20 g of 9,9-bis(4-hydroxyphenyl)fluorene and 9.5 g of 1,4-bismethoxymethylbenzene were added with 70 g of PGMEA, and 0.20 g of diethyl sulfate was added. After synthesis in the same manner as in Example 1, the result of GPC measurement of the obtained polymer compound was that the weight average molecular weight (Mw) in terms of standard polystyrene was 4,900.

[0036] Comparative Example 2 Except for changing the reaction time to 5 hours, the synthesis was carried out in the same manner as in Comparative Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) in terms of standard polystyrene was 1,500.

[0037] Comparative Example 3 Except for changing the reaction time to 30 hours, the synthesis was carried out in the same manner as in Comparative Example 1. As a result of GPC measurement of the obtained polymer compound, the weight average molecular weight (Mw) calculated as standard polystyrene was 21,000.

[0038] Experimental Example 1 3.0 g of the polymer compound obtained in Example 1, 37.5 g of propylene glycol monomethyl ether acetate, 9.4 g of cyclohexanone, and 0.05 g of polyoxyethylene alkyl ether were added and dissolved by stirring for 20 hours. After filtering the solution through a 0.2 μm fine filter, a hard mask film-forming composition was prepared and applied onto a silicon wafer using a spin coater. The composition was heated on a hot plate at 240° C. for 1 minute and then continuously heated at 400° C. for 1 minute to form a hard mask film. Experimental Example 2 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 2 was used. Experimental Example 3 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 3 was used. Experimental Example 4 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 4 was used. Experimental Example 5 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Example 5 was used. Experimental Example 6 The same procedure as in Experimental Example 1 was repeated except that 17.0 g of the polymer compound obtained in Example 1, 26.35 g of propylene glycol monomethyl ether acetate, 6.6 g of cyclohexanone, and 0.05 g of polyoxyethylene alkyl ether were used. Experimental Example 7 The same procedure as in Experimental Example 6 was repeated, except that 17 g of the polymer compound obtained in Example 2 was used. Experimental Example 8 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Example 3 was used. Experimental Example 9 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Example 4 was used. Experimental Example 10 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Example 5 was used. Experimental Example 11 The same procedure as in Experimental Example 1 was repeated except that 3.0 g of the polymer compound obtained in Example 1, 37.5 g of propylene glycol monomethyl ether acetate, 9.4 g of cyclohexanone, and 0.025 g of polyoxyethylene alkyl ether were used. Experimental Example 12 The same procedure as in Experimental Example 1 was repeated except that 3.0 g of the polymer compound obtained in Example 1, 37.595 g of propylene glycol monomethyl ether acetate, 9.4 g of cyclohexanone, and 0.005 g of polyoxyethylene alkyl ether were used.

[0039] Comparative Experiment Example 1 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Comparative Example 1 was used. Comparative Experiment Example 2 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Comparative Example 2 was used. Comparative Experiment Example 3 The same procedure as in Experimental Example 1 was repeated, except that 3.0 g of the polymer compound obtained in Comparative Example 3 was used. Comparative Experiment Example 4 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Comparative Example 1 was used. Comparative Experiment Example 5 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Comparative Example 2 was used. Comparative Experiment Example 6 The same procedure as in Experimental Example 6 was repeated, except that 17.0 g of the polymer compound obtained in Comparative Example 3 was used. Comparative Experiment 7 The same procedure as in Experimental Example 1 was repeated except that 17.0 g of the polymer compound obtained in Example 1, 26.4 g of propylene glycol monomethyl ether acetate, 6.6 g of cyclohexanone, and 0 g of polyoxyethylene alkyl ether were used. Comparative Experiment Example 8 The same procedure as in Experimental Example 1 was repeated except that 3.0 g of the polymer compound obtained in Example 1, 37.1 g of propylene glycol monomethyl ether acetate, 9.4 g of cyclohexanone, and 0.5 g of polyoxyethylene alkyl ether were used.

[0040] <Measurement of weight average molecular weight> The weight average molecular weights obtained in the above examples were measured by gel permeation chromatography (GPC) using a GPC device manufactured by WATERS under the following measurement conditions. Column temperature: 40°C, mobile phase: tetrahydrofuran (THF), flow rate: 1 mL / 1 min, GPC column: STYRAGEL KF-801, 802, 803 (WATERS, 8 x 300 mm) were used.

[0041] <Coating thickness characteristic test> The thickness of the hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 8 was measured, and the results are shown in Table 1. The measuring device used was an Ellipsometer (manufactured by Horiba, Ltd.).

[0042] [Table 1]

[0043] When the coating thickness of the hard mask film is 135 to 2,200, the coating property can be evaluated as good. When evaluating the coating thickness of the hard mask film, in Experimental Examples 1 to 12, the coating thickness of the hard mask film was measured to be 135 to 2,200 nm, and it was evaluated that the etch resistance was significantly excellent and the coating property was also significantly excellent.

[0044] In comparison, in Comparative Experimental Examples 1 and 2, the coating thicknesses were measured to be 130 and 100 nm, respectively, and it was evaluated that the etch resistance was significantly reduced. Also, in Comparative Experimental Examples 6 and 7, the coating thicknesses were measured to be 2,350 and 2,300 nm, respectively, and it was evaluated that the coating properties were poor due to the non-uniform physical properties of the coating surface. Here, in the case of Comparative Experimental Example 8, the compound of Example 1 was used, and the composition contained 1% polyoxyethylene alkyl ether based on the total weight of the composition. As a result of the coating thickness characteristic test shown in Table 1, it was measured to be 138 nm, and the coating property was evaluated to be good.

[0045] <Optical property testing> The refractive index n and extinction coefficient k of the hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 8 were measured, and the results are shown in Table 2. The measuring device used was an Ellipsometer (manufactured by Horiba, Ltd.).

[0046] [Table 2]

[0047] The refractive index (n@193 nm) and extinction coefficient (k@193 nm) of the hard mask film were measured as shown in Table 2, except for Comparative Experimental Example 6 and Comparative Experimental Example 7, which could not be measured due to poor coating properties. The refractive index (n@193 nm) of the hard mask film can be evaluated as excellent when it is 1.41 or less, and the extinction coefficient (k@193 nm) can be evaluated as excellent when it is 0.50 or less. First, the refractive index (n@193 nm) of the hard mask film was evaluated. In the cases of Experimental Examples 1 to 12, the refractive index (n@193 nm) of the hard mask film was measured to be 1.35 to 1.41, whereas in the cases of Comparative Experimental Examples 1 to 5, the refractive index (n@193 nm) was measured to be 1.44 to 1.45 (excluding Comparative Experimental Examples 6 and 7, which could not be measured due to poor coating properties). Therefore, it was confirmed that the refractive index (n@193 nm) characteristics were excellent in the cases of Experimental Examples 1 to 12.

[0048] Secondly, when evaluating the absorption coefficient (K@193 nm) of the hard mask film, in the cases of Experimental Examples 1 to 12, the absorption coefficient (K@193 nm) of the hard mask film was measured to be 0.46 to 0.50, whereas in the cases of Comparative Experimental Examples 1 to 5, the absorption coefficient (K@193 nm) of the hard mask film was measured to be 0.67 to 0.69 (excluding Comparative Experimental Examples 6 and 7, which could not be measured due to poor coating properties). Therefore, it was confirmed that the absorption coefficient (K@193 nm) characteristics of the hard mask film were significantly excellent in the cases of Experimental Examples 1 to 12.

[0049] Here, in Comparative Experimental Example 8, the compound of Example 1 was used, and the composition contained 1% polyoxyethylene alkyl ether based on the total weight of the composition. The refractive index (n@193 nm) of the hard mask film was measured to be 1.35, and the absorption coefficient (k@193 nm) was measured to be 0.48, which was evaluated as excellent.

[0050] <Evaluation of evaporation loss characteristics> The hard mask films formed in Experimental Examples 1 to 12 and Comparative Experimental Examples 1 to 8 were evaluated for evaporation weight loss characteristics. The weight loss was measured at 400° C. using a TGA (Thermal Analyzer System, manufactured by TA Instruments), and the measurement results are shown in Table 3.

[0051] [Table 3]

[0052] The evaporation weight loss characteristics of the hard mask film according to the prior art are known to be 4% or more in evaporation weight loss at 400° C. in TGA measurement, and therefore, a weight loss of less than 4% can be defined as excellent, and a weight loss of 3.5 to 3% can be defined as very excellent. In the case of Experimental Examples 1 to 12, the evaporation loss was measured to be 3%, whereas in the case of Comparative Experimental Examples 1 to 8, the evaporation loss was measured to be 4 to 11%, confirming that the evaporation loss characteristics of Experimental Examples 1 to 12 are extremely excellent. As described above, certain parts of the present invention have been described in detail, and it is obvious to those skilled in the art that such specific techniques are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention should be defined by the claims and their equivalents.

Claims

1. A spin-on hard mask composition comprising a polymer having a structure represented by the following formula 1 and a weight average molecular weight of 1,500 to 10,000: The spin-on hard mask composition is a spin-on carbon hard mask composition comprising, based on the total weight of the composition, 1 to 50 wt % of a polymer represented by the following Chemical Formula 1, 0.01 to 0.1 wt % of a surfactant, and 50 to 98.99 wt % of an organic solvent. 【Chemistry 1】 (In the formula, m and n are in the ranges of 1≦m≦50 and 1≦n≦50, respectively; R 1 teeth, 【change】 and R 2 teeth, 【change】 、 【change】 、 【change】 (It includes any of the following.)

2. 2. The spin-on carbon hard mask composition of claim 1, wherein the surfactant is selected from the group consisting of polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene nonyl phenyl ethers, polyoxyethylene octyl phenyl ethers, polyoxyethylene polyoxypropylenes, polyoxyethylene lauryl ethers, and polyoxyethylene sorbitans, or a mixture of two or more thereof.

3. 2. The spin-on carbon hard mask composition of claim 1, wherein the organic solvent is selected from the group consisting of propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone, cyclopentanone, γ-butyrolactone, ethyl lactate (EL), methyl ethyl ketone, n-butyl acetate, N-methylpyrrolidone (NMP), methyl 3-methoxypropionate (MMP), and ethyl 3-ethoxypropionate (EEP), or a mixture of two or more thereof.

4. A patterning method comprising the steps of applying the spin-on hard mask composition according to any one of claims 1 to 3 on top of a layer to be etched by spin coating, and baking to form a hard mask layer.

Citation Information

Patent Citations

  • Anti-reflective hard mask composition and method for patterning a material on a substrate using the same

    JP2010529499A

  • Spin on carbon hardmask compositions with characteristics of high etch resistance and patterning method by using the same

    KR101777687B1

  • Hardmask composition having antireflective property and method of patterning materials using the same

    KR1020080107210A

  • Spin on carbon hardmask compositions with characteristics of high thickness and patterning method by using the same

    KR102240213B1

  • Hardmask composition and method of forming patterns using the hardmask composition

    US20150332931A1